Acute central effects of alarin on the regulation on energy homeostasis. (August 2017) - Mikó, Alexandra; Füredi, Nóra; Tenk, Judit; Rostás, Ildikó; Soós, Szilvia; Solymár, Margit; Székely, Miklós; Balaskó, Márta; Brunner, Susanne M.; Kofler, Barbara; Pétervári, Erika
Abstract: Hypothalamic neuropeptides influence the main components of energy balance: metabolic rate, food intake, body weight as well as body temperature, by exerting either an overall anabolic or catabolic effect. The contribution of alarin, the most recently discovered member of the galanin peptide family to the regulation of energy metabolism has been suggested. Our aim was to analyze the complex thermoregulatory and food intake-related effects of alarin in rats. Adult male Wistar rats received different doses of alarin (0.3; 1; 3 and 15 μg corresponding approximately to 0.1, 0.33, 1, and 5 nmol, respectively) intracerebroventricularly. Regarding thermoregulatory analysis, oxygen consumption (indicating metabolic rate), core temperature and heat loss (assessed by tail skin temperature) were recorded in an Oxymax indirect calorimeter system complemented with thermocouples and Benchtop thermometer. In order to investigate potential prostaglandin-mediated mechanisms of the hyperthermic effect of alarin, effects of intraperitoneally applied non-selective (indomethacin, 2 mg/kg) or selective cyclooxygenase inhibitor (COX-2 inhibitor meloxicam, 1; 2 mg/kg) were tested. Effects of alarin on daytime and nighttime spontaneous food intake, as well as, 24-h fasting-induced re-feeding were recorded in an automated FeedScale system. Alarin increased oxygen consumption with simultaneous suppression of heat loss leading to a slow coordinated rise in core temperature. Both applied COX-inhibitors suppressed this action. Alarin failed to induce daytime food intake, but suppressed spontaneous nighttime and also fasting-induced re-feeding food intake. Alarin appears to elicit a slow anorexigenic and prostaglandin-mediated, fever-like hyperthermic response in rats. Such a combination would characterize a catabolic mediator. The potential involvement of alarin in sickness behavior may be assumed. Highlights: Alarin elicits a centrally coordinated, fever-like hyperthermic response in rats. Inhibition of prostaglandin synthesis suppresses thermoregulatory effects of alarin. Alarin reduces spontaneous night-time and fasting-induced re-feeding food intake. Alarin appears to be a catabolic neuropeptide. Alarin may participate in the development of sickness behavior.